A Review of Human Physiological Responses to Light: Implications for the Development of Integrative Lighting Solutions. Issue 3 (3rd July 2022) - Vetter, Céline; Pattison, P. Morgan; Houser, Kevin; Herf, Michael; Phillips, Andrew J. K.; Wright, Kenneth P.; Skene, Debra J.; Brainard, George C.; Boivin, Diane B.; Glickman, Gena
ABSTRACT: Architectural lighting has potent biological effects but applied lighting practices that capitalize on this potential have been limited. In this review, we endeavor to consolidate and synthesize key references that will be useful for lighting professionals, with the goal of supporting knowledge translation into pragmatic lighting strategies. Specifically, we explain relevant terminology, outline basic concepts, identify key references, provide a balanced overview of the current state of knowledge, and highlight important remaining questions. We summarize the physiological effects of light on human health and well-being, including a description of the processes underlying the photic regulation of circadian, neuroendocrine, and neurobehavioral functions. We review seminal work elucidating the elements mediating the potency of light for these physiological responses, with specific attention to factors critical for interpreting those findings. In parallel, we explain and endorse melanopic Equivalent Daylight Illuminance ( E v, m e l D 65 ) as the preferred measure to quantify the biological potency of light. Ultimately, while future studies are necessary to further facilitate the translation of laboratory knowledge to domestic and workplace settings, the immediate potential for applied lighting to better support human health is clear. Aiming for integrative lighting solutions that have biologically high potency light during the day and low potency during the night is perhaps the most immediate improvement to be made in order to better support applications for humans.